Addressing the Shortage of Health Professionals in Official Language Minority Communities to Strengthen Retention Strategies for the Benefit of New Brunswick Francophone and Acadian Communities: Protocol for a Mixed Methods Design - Collin, Stéphanie; Johnson, Claire; Dubé, Anick; Laforest, Marie-Eve; Lauzier, Martin; Landry, Michel H.; Cormier, Manon; Sonier-Ferguson, Brigitte (JMIR Research Protocols, 2023)
Background: COVID-19 has highlighted already existing human resource gaps in health care systems. New Brunswick health care services are significantly weakened by a shortage of nurses and physicians, affecting regions where Official Language Minority Communities (OLMCs) reside. Since 2008, Vitalité Health Network (the “Network”), whose work language is French (with services delivered in both official languages, English and French), has provided health care to OLMCs in New Brunswick. The Network currently needs to fill hundreds of vacant physician and nurse positions. It is imperative to strengthen the network’s retention strategies to ensure its viability and maintain adequate health care services for OLMCs. The study is a collaborative effort between the Network (our partner) and the research team to identify and implement organizational and structural strategies to upscale retention. Objective: The aim of this study is to support one of New Brunswick health networks in identifying and implementing strategies to promote physician and registered nurse retention. More precisely, it wishes to make 4 important contributions to identify (and enhance our understanding of) the factors related to the retention of physicians and nurses within the Network; determine, based on the “Magnet Hospital” model and the “Making it Work” framework, on which aspects of the Network’s environment (internal or external) it should focus for its retention strategy; define clear and actionable practices to help the Network replenish its strength and vitality; and improve the quality of health care services to OLMCs. Methods: The sequential methodology combines quantitative and qualitative approaches based on a mixed methods design. For the quantitative part, data collected through the years by the Network will be used to take stock of vacant positions and examine turnover rates. These data will also help determine which areas have the most critical challenges and which ones have more successful approaches regarding retention. Recruitment will be made in those areas for the qualitative part of the study to conduct interviews and focus groups with different respondents, either currently employed or who have left it in the last 5 years. Results: This study was funded in February 2022. Active enrollment and data collection started in the spring of 2022. A total of 56 semistructured interviews were conducted with physicians and nurses. As of manuscript submission, qualitative data analysis is in progress and quantitative data collection is intended to end by February 2023. Summer and fall 2023 is the anticipated period to disseminate the results. Conclusions: Applying the “Magnet Hospital” model and the “Making it Work” framework outside urban settings will offer a novel outlook to the knowledge of professional resource shortages within OLMCs. Furthermore, this study will generate recommendations that could contribute to a more robust retention plan for physicians and registered nurses.

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

Les Effets Potentiels de la Version Française du NCLEX-RN® sur le Choix de la Langue de Formation d'Étudiantes Infirmières Francophones en Situation Minoritaire. - Lalonde, Michelle; Chartrand, Julie; Vanderspank- Wright, Brandi; McGillis Hall, Linda; Gosselin-Bélanger, Amélie; Fullum, Jessica Adèle (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
Background: Since the introduction of the new entry to practice exam, the NCLEX-RN®, there has been a very low success rate among Francophone nursing students living in minority situations. In addition, there has been a drop in the number of candidates who choose to write the exam in French. These results are of great concern in terms of the quality and sustainability of French language health services in French language minority communities in Canada. Objectives: The purpose of this article is to present the results of a study exploring the experiences of students enrolled in an entry level nursing program in French in terms of their decision-making regarding: 1) the choice of the language of the nursing program in which they were enrolled, 2) the language in which they chose to write the NCLEX-RN®, 3) their interest in working in a Francophone context, 4) their general knowledge of the new entry to practice exam, and 5) information sources on the NCLEX-RN©. Methodology: A sequential mixed methods design using surveys with multiple-choice and open-ended questions was used to conduct this study. Descriptive analyzes, as well thematic and content analysis, were used to analyze the data. Results: 51 students from a francophone graduating cohort participated in this study. The majority of the participants expected to write the NCLEX-RN® in English; the media attention on the French version of the exam influenced their decision. Four main themes were highlighted : 1) Choice of language of student based on their first language, 2) Three main factors that influence the choice of the language in which they write the NCLEX-RN®, 3) Colleagues and media as sources of information on the NCLEX-RN®, and 4) Importance and pride of studying in French. Conclusion: The results of this project shed light on the factors that influence francophone students' decision-making regarding the choice of language for the exam and the reasons why graduating students would choose to study in French again or not. , Contexte : Un très faible taux de réussite a été remarqué chez les étudiantes infirmières francophones en situation minoritaire ainsi qu’une chute du nombre de candidates qui choisissent de passer en français le nouvel examen d’autorisation, le NCLEX-RN®, qui a été introduit en 2015. Ces données sont préoccupantes s’agissant de la qualité et de la pérennité des services de santé en français dans les régions linguistiques minoritaires au Canada. Objectifs : Le but de cet article est de présenter les résultats concernant les expériences des étudiantes inscrites dans un programme de formation initiale en sciences infirmières en français sur leur prise de décision quant à : 1) la langue du programme auquel elles se sont inscrites, 2) la langue dans laquelle elles ont choisi de passer le NCLEX-RN®, 3) leur intérêt à travailler dans un contexte francophone, 4) leurs connaissances générales relatives au nouvel examen d’autorisation et 5) les sources d’information sur le NCLEX-RN®. Méthodologie : Un devis de recherche mixte séquentiel a été retenu comportant l’utilisation de questionnaires. Des analyses descriptives et des analyses thématiques et de contenu ont été effectuées. Résultats : 51 étudiantes de la cohorte francophone ont participé à cette étude. La majorité des participantes comptaient passer le NCLEX-RN® en anglais; l’intérêt médiatique porté à la version française de l’examen a eu une influence sur leur décision. Quatre grands thèmes ont été mis en évidence à partir des questions à court développement du questionnaire : 1) langue maternelle choisie comme langue de formation, 2) trois principaux facteurs qui influencent le choix de la langue pour le NCLEX-RN®, 3) collègues et médias comme sources d’information sur le NCLEX-RN®, et 4) importance et fierté d'étudier en français. Conclusion : Les résultats de ce projet ont mis en évidence les facteurs qui influencent la prise de décision des étudiants francophones quant au choix de la langue de l’examen et les raisons pour lesquelles les finissantes étudieraient à nouveau en français.

Report on the 2020–2023 Café de Paris Manitoba Pilot Project - Roberge, Jérémie (Santé en français Manitoba, 2023)

Recruiting service providers with French proficiency: Tips and strategies - Schutte, Valerie; Erbach, Madison; Summers, Nikky; Jennings, Melissa (The Knowledge Institute on Child and Youth Mental Health and Addictions, 2023)

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.